Time Lapse Based Single Axis MPP Tracking System for Solar Tree by Using Arduino Duemalinove Board - Rajesh Babu, Damala; Rambabu, M. (International Journal of Engineering and Technology, 2018)
Extracting usable electricity was made possible by the discovery photoelectric mechanism and subsequent eventual evolution of aÂ  solar cell which is a semi conducting type that converts usable light into direct current.a hardware model of photovoltaic modules is proposed in this project. The objective of this project is to develop a solar tree model, in which the panels align themselves according to the movement of the sun and track maximum possible solar energy.The proposed model has panels mounted on a structure having a single axis solar tracking system with a view to assess the desired power and enhance the efficiency of solar conversion by consuming very less space relatively. Sunlight is tracked more effective by this tracking system by rotating pv panels in a single axis.In the tracking system optimum power is achieved by tracking the sun in all possible directions.A charge controller limits the rate at which the the electrical ower stored and used.Â Â